Multi-informant assessment of transition-related skills and skill importance in adolescents with autism spectrum disorder. (January 2018) - Hume, Kara; Dykstra Steinbrenner, Jessica; Sideris, John; Smith, Leann; Kucharczyk, Suzanne; Szidon, Kate
Adolescents with autism spectrum disorder have limited participation in the transition planning process, despite the link between active participation and an improvement in postsecondary education and employment outcomes. The Secondary School Success Checklist was designed to support transition planning for adolescents with autism spectrum disorder by incorporating their own assessments of strengths, skill deficits, and prioritization for instruction along with those of their parents and teachers across multiple skill domains. Findings from more than 500 adolescents with autism spectrum disorder across the United States indicate discrepancies between adolescent, teacher, and parent ratings of skills highlighting the importance of the inclusion of multiple perspectives in transition planning. Although ratings varied, agreement between adolescents with autism spectrum disorder, parents, and teachers across the highest and lowest rated skills suggests the need to broaden the focus on critical transition skills to include problem-solving, planning for life after high school, and self-advocacy.